PENGARUH KUALITAS AKUNTANSI MANAJEMEN DALAM PENGAMBILAN KEPUTUSAN PENDAPATAN PADA PT. PEGADAIAN (PERSERO) CABANG NGANJUK - Dyah Septiani; Sri Rahayuningsih (Gapenas Publisher, 2023)
This study aims to identify and analyze the effect of the quality of management accounting on making a decision on income at PT Pegadaian (Persero) Nganjuk Branch. The method used is a quantitative method with a descriptive approach using primary data from the results of a questionnaire with a sample of 30 employee respondents. The classical assumption regression model is used to explain the characteristics of the respondents, while the multiple regression test tool is a data analysis tool used to explain the description of the research. The data that has been obtained is processed through the SPSS 26.0 statistical program. The results of the study explain that management accounting quality variables influence earnings decisions, shown in the results of a simple linear regression using a partial test, where the results of the partial test of variable X have a t-count value of 5.982 > t-table value of 2.024 with a significance value of 0.000 not exceeding 0.05. The coefficient of determination (R square / R²) is the percentage of influence of the independent variable on the dependent variable, R square is 0.561, which means that the influence of the Y variable (income decision making) is 56.1%. It can be concluded that the quality of management accounting (X) on revenue decision making (Y) has a significant positive impact partially, this is because good management accounting quality can improve the quality of income decision making through the selection of appropriate and relevant decisions